Missing Leadership Talent Pool: Resolving Strategic Issues in Higher Education Succession Planning Through Developmental Relationship (S/O 14624) - Muslim, Sakinah; Zainal Abidin, Nor Azizah; Osman, Sharifuzah; Abdul Manaf, Halimah (UUM, 2023)
The developmental relationship is commonly implemented in HEIs to support the learning of potential leaders. However, significant effort needs to be devoted to a structured process to ensure the effectiveness of this developmental relationship. Hence, this study was conducted to examine the nature of the coaching and mentoring system as a component of developmental relationships and how this effort plays its role in fostering leadership skills in HEIs. This study is critically important because it will contribute to the breadth of literature on leadership development and how a coaching and mentoring component can enhance leadership development, especially in HEIs. Using a qualitative approach, data were collected from five participants from five Public Universities in Malaysia. Data was collected using interviews with a focus on the main issues in the leadership talent pool and how developmental relationship practices will accommodate succession planning in Malaysian higher education institutions. Issues for the current practices were identified and these include leadership skills and academic competencies, political elements, utilization of external experts, and the perception that the leadership role is a burden. In terms of implementation, coaching, and mentoring are relatively at the infancy stage for most institutions. Also, the effectiveness of the initiatives is largely influenced by the inclusion of shared values and goals institution, the role played by top management, and the presence of profiling, and psychometric tests. The study found that the effectiveness of coaching and mentoring programs in providing support for a new leader in a leadership position in the development of skills necessary to become a leader in HEIs is perceived as acceptable. The study recommends looking at succession planning in a more critical and reflective light for the benefit of potential leaders and higher education institutions at large. Based on the finding, the researcher come-out with a model of the talent pool in Malaysia that include robust and inclusive development opportunities to assist individuals in advancing within the institution.